A case study of the coconut crab Birgus latro on Zanzibar highlights global threats and conservation solutions. Issue 4 (22nd July 2021) - Caro, Tim; Hamad, Haji; Rashid, Rashid Suleiman; Kloiber, Ulrike; Morgan, Victoria M.; Nokelainen, Ossi; Caro, Barnabas; Pretelli, Ilaria; Cumberlidge, Neil; Borgerhoff Mulder, Monique
Abstract: The coconut crab Birgus latro, the largest terrestrial decapod, is under threat in most parts of its geographical range. Its life cycle involves two biomes (restricted terrestrial habitats near the coast, and salt water currents of the tropical Indian and Pacific Oceans). Its dependence on coastal habitat means it is highly vulnerable to the habitat destruction that typically accompanies human population expansion along coastlines. Additionally, it has a slow reproductive rate and can reach large adult body sizes that, together with its slow movement when on land, make it highly susceptible to overharvesting. We studied the distribution and population changes of coconut crabs at 15 island sites in coastal Tanzania on the western edge of the species' geographical range. Our aim was to provide the data required for reassessment of the extinction risk status of this species, which, despite indications of sharp declines in many places, is currently categorized on the IUCN Red List as Data Deficient. Pemba Island, Zanzibar, in Tanzania, is an important refuge for B. latro but subpopulations are fragmented and exploited by children and fishers. We discovered that larger subpopulations are found in the presence of crops and farther away from people, whereas the largest adult coconut crabs are found on more remote island reserves and where crabs are not exploited. Remoteness and protection still offer hope for this species but there are also opportunities for protection through local communities capitalizing on tourist revenue, a conservation solution that could be applied more generally across the species' range.